Comparison between virus Shedding and Fever Duration after Treating Children with Pandemic a H1N1/09 and Children with a H3N2 with a Neuraminidase Inhibitor. Issue 1 (January 2015) - Sugaya, Norio; Sakai-Tagawa, Yuko; Bamba, Masahiro; Yasuhara, Rieko; Yamazaki, Masahiko; Kawakami, Chiharu; Yamaguchi, Yoshio; Ide, Yoshiaki; Ichikawa, Masataka; Mitamura, Keiko; Kawaoka, Yoshihiro
Background: Shedding of the pandemic virus during an influenza pandemic is thought to persist longer than shedding of influenza viruses during annual influenza seasons, because people have much less immunity against a pandemic influenza. A correlation is thought to exist between the length of virus shedding and the clinical severity of influenza illness. Methods: We compared the virus isolation rates of children with pandemic A H1N1/09 influenza infection and children with A H3N2 influenza infection after the patients had been treated with one of three neuraminidase inhibitors (NAI) such as peramivir, laninamivir and oseltamivir. The clinical effectiveness of each NAI was assessed on the basis of the duration of the febrile period after the start of treatment. Results: Influenza viruses were isolated from 15 of the 34 patients in the A H3N2 group (mean age 6.2 years) and from 4 of the 25 patients in the A H1N1/09 (mean age 5.6 years) virus group (44.1% versus 16.0%; P <0.05). However, the differences between the duration of fever in the patients in the A H3N2 group and A H1N1/09 group after treatment with the NAIs were not significant. Conclusions: The virus isolation rates after treatment with each of the NAIs were significantly lower in the A H1N1/09 group, suggesting that the pandemic A H1N1/09 virus was more sensitive to the NAIs than the seasonal A H3N2 virus was. Clinically, there were no significant differences in the effectiveness of the NAIs between the H1N1/09 infected group and H3N2 infected group.